Stationary dislocation motion at stresses significantly below the Peierls stress: Example of shuffle screw and 60∘ dislocations in silicon. (March 2021) - Chen, Hao; Levitas, Valery I.; Xiong, Liming; Zhang, Xiancheng
Graphical abstract: Abstract: The stationary motion of shuffle screw and 60 ∘ dislocations in silicon when the applied shear, τ a p, is much below the static Peierls stress, τ p max, is proved and quantified through a series of molecular dynamics (MD) simulations at 1 K and 300 K, and also by solving the continuum-level equation of motion, which uses the atomistic information as inputs. The concept of a dynamic Peierls stress, τ p d, below which a stationary dislocation motion can never be possible, is built upon a firm atomistic foundation. In MD simulations at 1 K, the dynamic Peierls stress is found to be 0.33 G P a for a shuffle screw dislocation and 0.21 G P a for a shuffle 60 ∘ dislocation, versus τ p max of 1.71 G P a and 1.46 G P a, respectively. The critical initial velocity v 0 c ( τ a p ) above which a dislocation can maintain a stationary motion at τ p d < τ a p < τ p max is found. The velocity dependence of the dissipation stress associated with the dislocation motion is then characterized and informed into the equation of motion of dislocation at the continuum level. A stationary dislocation motion below τ p max is attributed to: (i) the periodic lattice resistance smaller than τ p max almost everywhere; and (ii) the change of a dislocation's kinetic energy, which acts in a way equivalent to reducing τ p max . The results obtained here open up the possibilities of a dynamic intensification of plastic flow and defects accumulations, and consequently, the strain-induced phase transformations. Similar approaches can be applicable to partial dislocations, twin and phase interfaces.